Ferdinand's Bridge, Vienna - Warren, Charles (engraver):::Creator::::::::::::; Winkcles, B. (artist):::Contributor:::::::::::: (Brain & Payne; London; United Kingdom)
Engraving of Ferdinandsbrücke in Vienna from the mid-nineteenth century.